2009
DOI: 10.1111/j.1439-0531.2008.01060.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose–Response Studies for Pituitary and Testicular Function in Male Dogs Treated with the GnRH Superagonist, Deslorelin

Abstract: We tested the effect of dose of GnRH superagonist on pituitary and testicular function in a study with four groups of four male dogs. The Controls received blank implants and the other three groups received implants containing 3, 6 or 12 mg deslorelin (D-Trp6-Pro9-des-Gly10-GnRH ethylamide). In all deslorelin-treated groups, there was initially an acute increase in plasma concentrations of LH and testosterone, followed by declines such that both hormones became undetectable after approximately 12 days. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
57
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 18 publications
15
57
1
1
Order By: Relevance
“…The results demonstrated that GnRH agonist immunization can promote the synthesis and secretion of FSH. Our results were consistent with the reports of Guo and Gao (2005), Junaidi et al, (2009), andGong et al (2011), but unfamiliar with other reports (Zamaratskalia et al, 2007;Li et al, 2009). Whether the efficacies of GnRHa are associated with the oestrous and/or ovulation of ewes and injection dosage of alarelin antigen needs to be further explored.…”
Section: Discussionsupporting
confidence: 94%
“…The results demonstrated that GnRH agonist immunization can promote the synthesis and secretion of FSH. Our results were consistent with the reports of Guo and Gao (2005), Junaidi et al, (2009), andGong et al (2011), but unfamiliar with other reports (Zamaratskalia et al, 2007;Li et al, 2009). Whether the efficacies of GnRHa are associated with the oestrous and/or ovulation of ewes and injection dosage of alarelin antigen needs to be further explored.…”
Section: Discussionsupporting
confidence: 94%
“…As experienced so far, reversibility accounts for all the effects resulting from hormonal castration, including semen quality (Junaidi et al. 2003, 2009; Ludwig et al.…”
Section: Introductionmentioning
confidence: 98%
“…Azoospermia and/or an ejaculation were observed at 60 weeks (3 mg implant) and 90 weeks (12 mg) post‐implantation (Junaidi et al. ) and after 3 months when using a 4.7 mg deslorelin implant (Romagnoli et al. ).…”
Section: Gonadotropin Hormone Releasing Agonists and Antagonistsmentioning
confidence: 99%
“…Complete return of semen quality to pre‐treatment values was observed by 62 (3 mg) to 102 (12 mg) weeks post‐implantation (Junaidi et al. ).…”
Section: Gonadotropin Hormone Releasing Agonists and Antagonistsmentioning
confidence: 99%